Performance-based financing in low income and middle-income countries: isn’t it time for a rethink? - Paul, Elisabeth; Albert, Lucien; N’Sambuka Bisala, Badibanga; Bodson, Oriane; Bonnet, Emmanuel; Bossyns, Paul; Colombo, Sandro; De Brouwere, Vincent; Dumont, Alexandre; Gyselinck, Karel; Ooms, Gorik; Samb, Oumar M.; et al. (BMJ global health, 2018)
This paper questions the view that performance-based financing (PBF) in the health sector is an effective, efficient and equitable approach to improving the performance of health systems in low-income and middle-income countries (LMICs). PBF was conceived as an open approach adapted to specific country needs, having the potential to foster system-wide reforms. However, as with many strategies and tools, there is a gap between what was planned and what is actually implemented. This paper argues that PBF as it is currently implemented in many contexts does not satisfy the promises. First, since the start of PBF implementation in LMICs, concerns have been raised on the basis of empirical evidence from different settings and disciplines that indicated the risks, cost and perverse effects. However, PBF implementation was rushed despite insufficient evidence of its effectiveness. Second, there is a lack of domestic ownership of PBF. Considering the amounts of time and money it now absorbs, and the lack of evidence of effectiveness and efficiency, PBF can be characterised as a donor fad. Third, by presenting itself as a comprehensive approach that makes it possible to address all aspects of the health system in any context, PBF monopolises attention and focuses policy dialogue on the short-term results of PBF programmes while diverting attention and resources from broader processes of change and necessary reforms. Too little care is given to systemwide and long-term effects, so that PBF can actually damage health services and systems. This paper ends by proposing entry points for alternative approaches.
Keywords: middle-income countries; health sector